2003
DOI: 10.1007/bf03020185
|View full text |Cite
|
Sign up to set email alerts
|

Trends in opioid use for chronic neuropathic pain: a survey of patients pursuing enrollment in clinical trials

Abstract: P Pu ur rp po os se e: : Clinical trials suggest that opioids relieve neuropathic pain and decrease pain-related disability. We conducted a pilot study of current prescribing trends and patients' attitudes towards opioids for neuropathic pain.M Me et th ho od ds s: : A patient questionnaire was completed by individuals pursuing enrollment in neuropathic pain clinical trials at our facility.R Re es su ul lt ts s: : Of 154 patients with diabetic neuropathy (55.2%), postherpetic neuralgia (29.9%), idiopathic peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…This increase is due in part to the study‐defined incorporation of PGB to this group of patients. This is in concordance with other first‐line treatments available among the current drug options, and which include tricyclic antidepressants and opioids 45 . In the present study, we recorded an important use of NSAIDs in the management of neck pain.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This increase is due in part to the study‐defined incorporation of PGB to this group of patients. This is in concordance with other first‐line treatments available among the current drug options, and which include tricyclic antidepressants and opioids 45 . In the present study, we recorded an important use of NSAIDs in the management of neck pain.…”
Section: Discussionsupporting
confidence: 87%
“…If it is accepted that by definition all the patients in the PGB group received at least one antiepileptic drug (ie, PGB), then the results of the drug use analysis indicate that this pharmacological group was employed concomitantly in a significantly greater proportion among the patients in the UC group, both before and during the study. This percentage reached 25% in the latter patient group, despite the fact that the lack of appropriate clinical trials does not allow us to establish clear recommendations for the combined use of several drugs in treating chronic NeP 44,45 . The changes in health outcome in turn were reflected in the costs of the disease.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In fact, a recent survey of neuropathic pain patients has indicated that a considerable proportion of patients are being prescribed combinations of analgesic drugs for neuropathic pain [15]. This is being performed in the absence of evidence to support polypharmacy, and the need to study combination therapy in neuropathic pain has recently been emphasized [7].…”
mentioning
confidence: 99%
“…Various barriers are found for initiating opioids therapy for chronic pain and commonest barriers to opioid therapy for neuropathic pain include patient/s, and possibly physician/s, fears of addiction and adverse effects. 14 It is feared that habitation and/or addiction may occur negating the efficacy of therapy and leading to major problems of its own. 9,15 However, drug abuse in patients, whose narcotic intake is rigidly controlled by their physician, is extremely rare.…”
Section: Discussionmentioning
confidence: 99%